Kynurenic acid as a biochemical factor underlying the association between Western-style diet and depression: A cross-sectional study - Francis, Heather M.; Stevenson, Richard J.; Tan, Lorraine S. Y.; Ehrenfeld, Lauren; Byeon, Sooin; Attuquayefio, Tuki; Gupta, Dolly; Lim, Chai K. (Frontiers in Nutrition, 2022)
Consumption of a Western-style diet (WS-diet), high in saturated fat and added sugar, is associated with increased depression risk. However, the physiological mechanisms underlying the relationship requires elucidation. Diet can alter tryptophan metabolism along the kynurenine pathway (KP), potentially linking inflammation and depression. This study aimed to examine whether urinary inflammatory markers and KP metabolites differed according to WS-diet consumption and depression severity. Depression symptoms and habitual WS-diet consumption were assessed in 169 participants of otherwise healthy adults aged 17–35. Targeted metabolomics profiling of seven KP metabolites, ELISA-based assays of interleukin-6 (IL-6) and C-reactive protein (CRP) were performed using urine samples collected from the participants. Parametric tests were performed for group comparison and associations analysis. Multilevel mixed-effect modelling was applied to control for biases. Higher intake of WS-diet was associated with lower levels of neuroprotective kynurenic acid (KA; R = – 0.17, p = 0.0236). There were no differences in IL-6 or CRP across diet groups (p<0.05). Physical activity had negative associations with most KP metabolites. Mixed-effects regression analysis showed the glutamatergic inhibitor, KA, was the only biomarker to have a significant association with depression symptoms in a model adjusted for demographic and lifestyle variables: a unit increase in KA was associated with 0.21 unit decrease in DASS-21 depression score (p = 0.009). These findings suggest that urinary KA is associated with both habitual WS-diet intake, and levels of depression symptoms, independent of inflammation. Findings support the role of neuroprotection and glutamatergic modulation in depression. We propose that KA may act as endogenous glutamatergic inhibition in regulating depression severity in the absence of inflammation. Further comparison with blood-based markers will assist in validating the utility of non-invasive urine samples for measuring KP metabolites.